PENGEMBANGAN MEDIA PSIKOEDUKASI BERBASIS VIDEO ANIMASI UNTUK PENCEGAHAN POSTPARTUM BLUES IBU POST SECTIO CAESAREA (SC) - Handayani, Ina; Supliyani, Elin; Susilawati, Enung Harni (Poltekkes Kemenkes Bandung, 2025)
Childbirth with Sectio Caesarea (SC) has risks, namely slower recovery due to wounds and pain so that the mother cannot care for her baby properly. This condition reduces the mother's confidence in carrying out her role, disrupts the natural attachment process and increases the occurrence of postpartum blues. Psychoeducation is important to prevent this from happening. Effective and easy to understand media regarding psychoeducation for postpartum mothers can be provided through animated videos. Information through animated videos is easier to understand and easier to store in memory for a longer period of time. The aim of this research was to produce animated video-based psychoeducational media. The research uses research and development research methods. The development procedure is carried out through: 1) Preliminary study stage, 2) Media development stage which is divided into 3 parts, namely a) compiling material, b) creating a script and preparing storyboards, c) making and editing videos. Next, validate the assessment by 1 media expert, 2 material experts and 5 post SC mothers in a limited trial to assess the suitability of the educational media created. The research results showed that animated video-based psychoeducation media had a feasibility level of 96 based on media expert assessment, while material expert assessment had a value of 90 and the result of limited trials had a value of 98. Animated video-based psychoeducation media for post-SC mothers is in the very feasible and positif category. Midwives can provide psychoeducation through animated videos.